Flow behavior caused by air permeability of ski jumping suit fabric - Kataoka, Y.; Hasegawa, H.; Murakami, M.; Seo, K.; Obayashi, S. (Proceedings, 2020)
The purpose of this study was to investigate the effect of the air permeability of ski jumping suit fabric on aerodynamic characteristics. In the study, four types of fabric with different air permeabilities were installed onto a fabric-clothed elliptic cylinder, and the flow behavior around its surface was investigated through wind tunnel experiments. The stall was delayed by using the fabric with higher air permeability. The air flow permeated the surface of the elliptic cylinder through the fabric for the fabric with high air permeability. This air flowed out into the separation region through the fabric again, which suppress stall. The stall characteristics for the fabric-clothed elliptic cylinder were influenced by the air permeability of the fabric. The boundary layer thickness on the outer surface and the turbulence levels of the boundary layer affected the air permeability of the fabric. The higher air permeability fabrics improved the stall characteristics.